(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
India is having its own role in the international level and it is it is contributing its role to world peace. As a biggest democratic nation, India is having its own prestigious role in the international level. Being a peaceful nation, India had got the independence by using the weapons like truth and non-violence. Its freedom movement can be termed as bloodless revolution. It means without bloodshed, it has attained its independence and it had given the message of peace to the other nations. Being a peace loving nation, it is a member of U.N.O, SAARC, ASEAN, COMMONWEALTH group of NATIONS, it is contributing to the world peace. Adopting the modern economy, it is adopted globalization, privatization, as a member of GATT agreement rtc it is considered as a fastly developing nation . AS a second biggest democratic nation, it is spreading the democratic values in the world. As a strong supporter of the U.N.O it is providing its military forces as peace keeping army to contribute to the world peace. As an independent and sovereignty nation, it encouraged the African can nations, to get freedom and strongly opposed colonialism. IN this paper, we are explain and presenting the terms as a role of India in the international level.